Infantile orbital abscess caused by methicillin-resistant Staphylococcus aureus: a case report and literature review - Qin, Yanran; Huo, Junming; Liu, Chengjun; Fu, Yueqiang; Li, Jing (Frontiers in Pediatrics, 2023)
Objective: To report and review infantile orbital abscess caused by methicillin-resistant Staphylococcus aureus (MRSA).We report a case of MRSA-induced infantile orbital abscess accompanied by sepsis, pneumonia, and purulent meningitis. We systematically review cases of MRSA-induced infantile orbital abscess published in PubMed, Web of Science and ScienceDirect until April 2023.We reviewed 14 patients (our patient + 13 patients [10 papers] identified via literature searches). There were 9 boys and 5 girls; 9 neonates and 5 older infants; and 8 full-term births and 1 preterm birth. The gestational age at birth was unknown for 5 infants. The right and left orbits were affected in 10 and 4 patients, respectively. The clinical presentation included periorbital soft-tissue edema or redness (11 patients), fever (7 patients), exophthalmos (10 patients), limited eye movement (4 patients), purulent eye secretions (2 patients), and skin abscess and convulsion (1 patient each).The source of infection was sinusitis (8 patients), vertical transmission, gingivitis, dacryocystitis, upper respiratory tract infection (1 patient each), and unknown (2 patients). MRSA was detected in blood (6 patients) or pus culture (8 patients).Vancomycin or linezolid were used for 11 patients; corticosteroids were administered to only 1 patient. Surgical drainage was performed for 13 infants (external drainage, 11 patients; endoscopic drainage, 2 patients). Two patients initially had pulmonary and intracranial infections. Except for one patient with neurological dysfunction at discharge, all other infants had no sequelae or complications.Early aggressive anti-infective treatment and timely drainage are essential for managing MRSA-induced infantile orbital abscess.